National Agriculture Market: The Game Changer for Indian Farming Community - Abhishek Sharma, J.P. Yadav (International Journal of Scientific Research and Management (IJSRM), 2017)
With nearly 56 per cent of the population depending upon agriculture sector for their livelihood, the unification of markets both at State and National level is essential. Thus, last year Prime Minister launched National Agriculture Market portal (eNAM) on April 15, 2016, to connect e-mandies in several States. eNAM is an online inter-connectivity of e-mandies, aimed at marshalling the much needed agriculture marketing reforms to enable farmers to get better price of their produce The Government’s decision of creating this eplatform for farmers will remove inter-state barriers in moving farm produce and can be a game changer provided the requirements are fulfilled by states. These two most important requirements include amendment of the State Agricultural Produce Marketing Committee Act (APMC) Acts and physical logistic support to farmers which would enable them to move their crops, e-NAM has the potential to transform Indian agriculture from traditional to an entrepreneurial and a profit making venture.